Desenvolvimento de aluminas-y mesoporosas dopada com céria ezircônia pelo processo sol-gel para aplicações em catalisadoresautomotivos - Marcello Rosa Dumont (2016)
The burning of hydrocarbons in vehicle engines produces a complex mixture of pollutants gases that need to be converted to less harmful products. Currently the way most used to make this conversion is through a vehicular catalyst (where occurs a heterogeneous catalysis reaction of vapor phase) also called catalytic converter installed on the exhaust system of the vehicle. The majority of vehicular catalytic converters is constituted basically by ceramic materials and metals with catalyticproperties, such as Palladium, Platinum and Rhodium. These catalytic metals are dispersed on ceramic material and have high cost which makes the catalytic converter an expensive component. Several studies are conducted to improve the dispersion of these metals and increase the efficiency of catalysis thus reducing the content of these metals. The sol-gel route is often used to obtain ceramic materials with propertiessuperior to those obtained by conventional routes, including increased surface area and increased thermal resistance. In this thesis mesoporous -aluminas doped zirconia and zirconia were obtained with high dispersion, homogeneity and thermal stability for use in automotive catalyst systems, using sol-gel routes. These materials were prepared under acidic and basic conditions aided by simplex centroid design of experiments with response surface methodology. The presence of cubic and tetragonal phases of -Al2O3 with additional reflections attributed to CeO2 and ZrO2 were observed. The higher surface area and smaller pore sizes were observed for samples obtained in basic catalysis conditions and with intermediate concentrations of ceria and water. The association of mesoporous alumina doped ceria and zirconia to rigidtemplates and surfactants enabled the formation of hierarchical, ordered and interconnected mesoporous with great potential for the production of advanced ceramic materials. The samples synthesized in an ethanol medium and without added of water tended to form ordered mesopores with hexagonal SBA-15 symmetry. Samples with higher water and P123 content showed mesopores unordered formation trend with highsurface area and high dispersion of agglomerates.